The Relationship Between Brain/Behavioral Systems and Pain Anxiety Mediated by Distress Tolerance in Psychiatric Patients in Babol County - Asgharpour Miri , Maedeh; Pourfaraj Omran, Majid (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to examine the relationship between brain/behavioral systems and pain anxiety with the mediating role of distress tolerance in psychiatric patients in Babol County. Methods and Materials: The study employed a descriptive-correlational design using structural equation modeling (SEM). The statistical population included all psychiatric patients who referred to treatment centers in Babol County during 2024. A sample of 250 participants was selected using convenience sampling. Data collection was conducted using standardized instruments: Carver and White’s BIS/BAS Scales to measure brain/behavioral systems, the Pain Anxiety Symptoms Scale (PASS) by McCracken and Dhingra (2002), and the Distress Tolerance Scale by Simons and Gaher (2005). Data analysis was performed using SmartPLS software. The normality of data distribution was evaluated through the Kolmogorov–Smirnov test, and due to non-normal distributions, variance-based SEM techniques were applied. Reliability and validity of the measurement models were assessed using composite reliability, Cronbach’s alpha, Average Variance Extracted (AVE), and discriminant validity via the Fornell-Larcker criterion. Findings: The results indicated a significant positive relationship between brain/behavioral systems and pain anxiety (β = 0.635, p < 0.001), and a significant negative relationship between brain/behavioral systems and distress tolerance (β = 0.973, p < 0.001). Additionally, distress tolerance was found to significantly predict lower levels of pain anxiety (β = 0.148, p < 0.001). The Sobel test confirmed the mediating role of distress tolerance in the relationship between brain/behavioral systems and pain anxiety (Z = 6.998, p < 0.001), thus supporting the fourth hypothesis of the study. Conclusion: The findings suggest that distress tolerance plays a critical mediating role in the link between neural reactivity (BIS/BAS activity) and pain-related anxiety among psychiatric patients. Enhancing distress tolerance may therefore be a valuable therapeutic target for reducing pain anxiety in clinical populations.